A SENSE OF COHERENCE AS A FACTOR IN AN INDIVIDUAL’S WELL-BEING - Павленко, Ганна Володимирівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2020)
The article is devoted to the study of well-being, which is considered as a multi-factorial construct and is described by most scientists in three terms: «subjective well-being», «life satisfaction» and «psychological well-being». The article covers the theoretical analysis of the concepts of «psychological well-being» and «subjective well-being», and also the concept of «coherence». Psychological well-being is considered as a basic dynamic characteristic of a personality, which reflects a subjective assessment by a person of his functioning and potential capabilities. Subjective well-being is considered as an integral system, which consists of the personality's ideas about himself, his life, his relations, capabilities.The concept of «sense of coherence» is considered as an orientation of a person to what extent a person perceives life as conscious and amenable to control. The empirical study involved 251 people, of whom 197 were women and 54 men, the average age was 27-41. Four test methods and two statistical-mathematical methods were used. The results of the study of the correlation between the sense of coherence and the level of psychological and subjective well-being among students are presented. The specificity of correlation between the components of coherence (comprehensibility, manageability, meaningfulness) and indicators of well-being is considered. A correlation analysis was performed to detect the relationships between the components of a sense of coherence and psychological well-being. For a visual representation, the results obtained are presented in the form of diagrams. Regression analysis was used to study the effect of sense of coherence on psychological well-being. It was revealed that sense of coherence is a factor of ensuring the psychological well-being. Further perspectives for psychological well-being research have been identified.  Further perspectives are in clarification of the concept of psychological well-being and the study of the characteristics of the relationship of psychological and subjective well-being with various dispositions of an individual.